Análise da produção científica em programas de pós-graduação em geografia no Brasil (1987-2006) - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
This study inventories, describes and analyzes the research in the Graduate Programs in Geography in Brazil from 1987 to 2006. We analyzed 3992 titles of theses and dissertations. Bibliographic data and abstracts of the papers were obtained from the Bank of Theses of the Coordination of Improvement of Higher Education Personnel (CAPES). The summaries were analyzed according to the proposed content analysis of Bardin (1977). The results reveal a field of field of Human Geography, a decline in the proportion of jobs in the area of Physical Geography and a growing trend of environmental studies.
Keywords: Geografia; Estado da Arte; Pós-graduação; Produção Geográfica; Geography; State of the Art; Postgraduate; Geographical Production; CIÊNCIAS HUMANAS: GEOGRAFIA